2006
DOI: 10.1111/j.1525-1438.2006.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Crk SH3 domain-binding guanine nucleotide-releasing factor (C3G) in cervical squamous cell carcinoma

Abstract: C3G, a Crk SH3 domain-binding guanine nucleotide-releasing factor functions as a guanine nucleotide exchange factor for Rap1. It is activated via the Crk adaptor protein and plays an important role in transducing signals from receptors on the cell surface to the nucleus via the Ras/Raf/MAPK signal transduction pathway. However, since the experimental data result in pleiotropic effects in the cascade manner, its precise function remains unclear. Here we examined the C3G expression in cervical squamous cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The physiological pro-apoptotic role of P2X 7 in these cells was previously demonstrated [7,8,13]. Previous studies in cervical cells have also identified tumor suppressor genes [33][34][35][36][37][38][39][40][41][42][43][44][45][46] and apoptosis-related genes [35,39,43,44,[46][47][48][49] that are regulated by changes in DNA methylation. However, until recently, little was known about the effects of DNA methylation on P2X 7 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological pro-apoptotic role of P2X 7 in these cells was previously demonstrated [7,8,13]. Previous studies in cervical cells have also identified tumor suppressor genes [33][34][35][36][37][38][39][40][41][42][43][44][45][46] and apoptosis-related genes [35,39,43,44,[46][47][48][49] that are regulated by changes in DNA methylation. However, until recently, little was known about the effects of DNA methylation on P2X 7 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…We further analyzed a 373-bp region within CGI-A covering the CpG sites previously analyzed by Okino et al, in cervical squamous carcinomas (10). We found no traces of methylation in any of 29 tumor samples (Fig.…”
Section: Methylation Status Of Rapgef1 In Cervical and Ovarian Cancersmentioning
confidence: 63%
“…Recently, promoter hypermethylation of RAPGEF1 was suggested as a gene silencing mechanism in cervical squamous cell carcinomas (10). A frequency of hypermethylation of 38% (5/13) in cervical tumors of the strict-criterion CpG island (CGI-A), was reported using methylation-sensitive PCR (MSP) (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that paxillin phosphorylation in human colon cancer cells in response to pressure facilitates paxillin-Crk binding, which is also required for the stimulation of adhesion. Further study may clarify whether pressure-induced signaling prior to adhesion also involves such known Crk-binding partners in adherent cells as DOCK180 or C3G [50,51].…”
Section: Discussionmentioning
confidence: 99%